The Influence of Perceptions on Fisherman Understanding and Fish Traders and Management Strategies of Sharks and Rays in Conservation Status in Cilacap Regency - Rianto, Joko; Riani, Etty; Warlina, Lina (Politeknik Kelautan dan Perikanan Karawang, 2023)
Cilacap Regency is one of the giant Shark and ray landing sites on the south coast of Java. Engagement in fisheries management, such as RFMOs and CITES, requires regulations governing the use of sharks and rays in Indonesia. The successful application of these rules requires the support of fishermen and fish traders. The aim of the study was to determine the effect of the perceptions of fishermen and fish traders on the understanding of the management status of sharks and rays and management strategies. The research method uses a quantitative approach, instrument testing, and simple linear regression data analysis using SPSS 25 software. The Shark and Ray management strategy uses SWOT analysis. The results of the average social, economic interval (fisherman) level assessment were 2.27 (enough), perceptions of environmentally friendly fishing gear were 3.11 (good), perceptions of the existence of shark and ray resources were 2.52 (good), and the value of understanding indicators supported management of sharks and rays 2.27 (fairly understand). Assessment of social-economic indicators (fish traders) and perceptions 2.53 (good), perceptions of the existence of shark and ray resources 2.17 (adequate), and understanding in supporting shark and ray management 2.43 (comprehensive). The results of simple linear regression show that fishermen's socioeconomic indicators have a negative effect on understanding supporting Shark and ray management. Fishermen's perceptions of environmentally sound fishing gear, perceptions of the existence of shark and ray resources (fishermen and fish traders), and the socioeconomic conditions of fish traders have no influence on understanding supporting sharks and rays. The results of the SWOT analysis are in the Weakness and Opportunity cells, namely through efforts to limit products, increase the human resource capacity of business actors and related agencies, and ease of obtaining access to capital for fishermen.